Karakteristik Thalamitha sp. Hasil Tangkapan Samping Nelayan di Kota Tarakan sebagai Bahan Baku Pangan Bergizi: Fisheries By-Catch at Tarakan City as a source of Nutritious Food - Novi Luthfiyana; Stephanie Bija; Heni Irawati; Awaludin Awaludin; Andi Ramadani (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
Mottled swimming crab (Thalamita sp.) is one of the largest genus in the Portunidae subfamily having a smaller size and lower price compared to the other types of crab. Mottled swimming crab is a by-catch of fishermen in the Tarakan city and could be developed as a food source. The purpose of this study was to determine chemical composition, fatty acid profile and heavy metal content of mottled swimming crab. Whole body of the crab except claws and carapace was analyzed. The results showed mottled swimming crab contained 70.05% moister, 9.89% protein, 0.25% fat, 13.02% ash, 2.52% crude fiber and 6.84% carbohydrates content. The crab contained saturated fatty acids (SFA) amounted to 12.64%, monounsaturated fatty acids (MUFA) 5.46% and polyunsaturated fatty acids (PUFA) 8.73%. The content of Cd, Hg and Pb was still below the maximum limit allowed by Indonesian National Standard. The Keraca crab is proven to be safe to use as food and nutritious.